Formulation and SPF Value Evaluation of Sunscreen Spray Gel Containing Lime Peel Extract (Citrus aurantifolia) - Ericasyifa Salsabila; Wulandari, Fitri; Evieta Rohana (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: High exposure to sunlight has adverse effects on the skin. Lime peel contains more than 60% flavonoids, presenting the potential to function as a sunscreen due to the presence of conjugated aromatic benzene groups, capable of absorbing UV-A or UV-B rays from the sun. To prevent skin damage, lime peel extract is formulated into a spray gel, as it has the ability to dry rapidly, enhancing overall comfort for consumers during application. Objective: To determine the influence of variation concentration of lime peel extract in the sunscreen spray gel on its physical properties and in vitro SPF value. Methods: Lime peel crude extract was obtained using 70% ethanol and formulated into a sunscreen spray gel at concentrations of 5%, 10%, and 15%. The spray gel formulation was evaluated for its physical quality and SPF value. Results: The variation in extract concentration has a statistically significant effect on the physical properties of the preparation and SPF values (P<0.05). The physical stability conditions in each formula (F1, F2, and F3) meet the requirements of the spray gel preparation in terms of pH, viscosity, spreading test, drying time test, and adhesion test. The spray gel preparations F1 (5%), F2 (10%), F3 (15%) each have SPF values of 20, 25, and 35 respectively. Conclusion: The spray gel formulations in F1 (5%), F2 (10%), and F3 (15%) are physically stable and have moderate to high SPF values, with F3 (15%) having the highest SPF value of 35.